S82 An Economic Evaluation Of Self-management Programs Delivered At Discharge After Acute Exacerbation, In Copd Patients In The Uk. (10th November 2014) - Blissett, D; Jowett, S; Jordan, R; Jolly, K; Turner, A; Barton, P
Abstract : This abstract summarises independent research funded by the National Institute for Health Research (NIHR) under its HTA Programme (Ref 11/27/01). The views expressed are those of the author (s) and not necessarily those of the NHS, the NIHR or the Department of Health. Background: Self-management interventions delivered to COPD patients at discharge following admission for exacerbation aim to enable patients to better manage and control their symptoms but it is not clear if they are beneficial. Our systematic review concluded that there was no evidence of a reduction in the risk of admissions or mortality but noted a dearth of good quality studies and a direction of effect for readmissions in favour of self-management. Methods: A hypothetical Markov model was built to estimate the cost-effectiveness of self-management interventions in COPD patients recently discharged from hospitals, compared to usual care. It estimated the effect in terms of Quality Adjusted Life Years (QALYs) in a cohort of UK COPD patients, applying a reduced risk of admissions obtained from the hazard ratio of 0.82 (0.50, 1.36) reported in a meta-analysis in a systematic review. Due to uncertainty around this effect, extensive sensitivity analysis was conducted to estimate the likelihood being cost-effective at alternative thresholds. Results: This model found that self-management delivered at discharge was more costly, but resulted in better outcomes, with a £683 cost difference and a gain of 0.0831 QALYs. To be cost-effective it would need to cost £2200 or less if the hazard ratio remained at 0.82. Sensitivity analysis found that self-management had a 68% probability of being cost-effective at a threshold of £20, 000 per QALY, with most of this uncertainty being around the effect, duration of effect and cost. Conclusion: If self-management interventions are effective in reducing readmissions for up to two years, they are likely to be cost-effective. This speculative economic model describes the uncertainty around this conclusion.